2016
DOI: 10.1363/psrh.12005
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Young Men's Intention to Discuss Birth Control with Female Partners

Abstract: CONTEXT Heterosexually active men who wish to prevent conception, but are not willing to use condoms consistently, need to discuss birth control with female partners. Improving the understanding of correlates of men’s intention to have such discussions is one step toward supporting this health-facilitating behavior. METHODS A sample of 372 heterosexually active men aged 18–25 were recruited and surveyed online between December 2010 and June 2011. Men answered questions on attitudes toward, norms regarding an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…Participants were men aged 18 -25. Questions were attitudes toward, norms regarding and self-efficacy n = 372 To examine men's intentions to discuss birth control with a female partner Masters, Morrison, Querna, Casey and Beadnell (2017) [7] Results showed that place of residence, marital status, religion, wealth, interaction with a health care provider, fertility preference, number of sexual partners and access to media were all significantly associated with modern contraceptive use among sexually active men [14] Study finding indicated that: -Men who were exposed to a religious leader speaking about FP were more likely to report using FP and discussing FP with their partner -Radio activities and television exposure was associated with FP use.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants were men aged 18 -25. Questions were attitudes toward, norms regarding and self-efficacy n = 372 To examine men's intentions to discuss birth control with a female partner Masters, Morrison, Querna, Casey and Beadnell (2017) [7] Results showed that place of residence, marital status, religion, wealth, interaction with a health care provider, fertility preference, number of sexual partners and access to media were all significantly associated with modern contraceptive use among sexually active men [14] Study finding indicated that: -Men who were exposed to a religious leader speaking about FP were more likely to report using FP and discussing FP with their partner -Radio activities and television exposure was associated with FP use.…”
Section: Resultsmentioning
confidence: 99%
“…From women perspectives men were seen as an obstacle and never enabled them to plan their next pregnancy [13]. Men engagement in family is affected by different factors [7] [8] [9] [10]. Attitudes, norms and self-efficacy were each positively associated with men's intention to discuss birth control [7].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Men consider contraception to be important and want to take on their reproductive responsibility [ 10 11 ]. However, despite wanting to avoid pregnancy, some men choose to enter sexual relationships without using contraception [ 12 ].…”
Section: Introductionmentioning
confidence: 99%